2007
DOI: 10.1007/s00221-007-1200-0
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of phonological processing in two distinct orthographies

Abstract: Recent fMRI studies comparing the processing of alphabetic versus logographic scripts provide evidence for shared and orthography-specific regions of neural activity. The present study used nearinfrared spectroscopy to compare (within and across brain regions) the time course of neural activation for these two distinct orthographies. Native readers of English and of Chinese were tested on a homophone judgment task. Differences across groups were obtained in the time course of hemodynamic change for the left mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…Even with the less powerful event-related design used here (but one that guards against carry-over effects), our results suggest that the NIRS method is capable of detecting subtle hemodynamic changes in complex language experiments, as suggested also by Chen et al [2008]. Because other studies have suggested that NIRS data are highly consistent with fMRI data, we anticipate seeing more research in the future using NIRS, as it is a more portable and affordable alternative to fMRI, as long as the ROI has been identified and is within the range of spatial resolution provided by NIRS [Strangman et al, 2002a].…”
Section: Discussionmentioning
confidence: 53%
“…Even with the less powerful event-related design used here (but one that guards against carry-over effects), our results suggest that the NIRS method is capable of detecting subtle hemodynamic changes in complex language experiments, as suggested also by Chen et al [2008]. Because other studies have suggested that NIRS data are highly consistent with fMRI data, we anticipate seeing more research in the future using NIRS, as it is a more portable and affordable alternative to fMRI, as long as the ROI has been identified and is within the range of spatial resolution provided by NIRS [Strangman et al, 2002a].…”
Section: Discussionmentioning
confidence: 53%
“…Research in the domain of reading has revealed that the network of language-processing regions typically associated with reading may be augmented by direct mappings between orthography and semantic content in Chinese readers. This additional mapping process may rely on activity in the rostrolateral aspect of the activation reported here (e.g., Chen, Vaid, Bortfeld, & Boas, 2008;Siok, Niu, Jin, Perfetti, & Tan, 2008;Booth et al, 2006;Kuo et al, 2004;Siok et al, 2004). Further work connecting these literatures may provide interesting insight into symbolic representation of numerosities in that Arabic numerals, like Chinese characters, are visual representations of abstract meaning that need not carry any phonetic information.…”
Section: Comparison > Recognition Taskmentioning
confidence: 88%
“…This association must be learned by rote memorization of Chinese characters, demanding an intensive coordination of various kinds of linguistic information contained in written Chinese (28,(30)(31)(32)(33)(34)(35). The left middle frontal gyrus is thought to be involved in the allocation and coordination of cognitive resources in working memory (36,37) and may therefore be recruited to serve this function (34,35,38).…”
Section: Discussionmentioning
confidence: 99%
“…These differences can lead to differences in how reading is supported in the brain. Readers of Chinese show relatively more engagement of visuospatial areas and left middle frontal regions for verbal working memory, presumably for recognizing complex, square-shaped characters whose pronunciations must be memorized by rote instead of being learned by using letter-to-sound conversion rules (31)(32)(33)(34)(35). In an fMRI study, we previously showed that, unlike impaired reading in English and other Western languages, impaired reading in logographic Chinese is associated with functional disruption of processes localized to the left middle frontal gyrus (28).…”
mentioning
confidence: 99%